Three phase induction motor coupled to DC motor in hybrid electric vehicle application - Zulkarnain, Lubis (2011)
An advanced electric drive controller for a high power starter-generator subsystem based on a series DC machine is presented. The machine is belt-coupled to a diesel engine in a series-parallel 2×2 HEV. The DC electric drive is developed for engine starting, generating and motoring. Computer simulations are performed for tuning the controller parameters, and for selecting proper inverter rating of the starter-generator drive. The drive controller is implemented in hardware using Lab Instruments Drive Technology with algorithm software fixed point digital signal processor (DSP) and a high resolution current sensing board to achieve the best torque regulation at various load conditions. The DC starter-generator has been tested in both motoring (engine starting) and generating modes with the starter-generator mounted in the vehicle. For the propulsion motor drive, three phase induction motor driven by a three-phase PWM inverter has been considered. The three phase induction motor drive cannot deliver high static and dynamic performance without the correct parameter values in the controller. Computer simulations showed the correct parameter variation effects on the performance of an induction motor drive used in an electric vehicle. A novel algorithm software mode observer based induction motor controller with on-line parameter adaptation is then presented. Software in the-loop (SIL) and hardware-in-the-loop (HIL) simulations have been performed for induction motor with electric vehicle load to verify the performance of the new algorithm as well as to tune the control parameters. For the HIL simulation, the controller was implemented in SIL based control hardware, and a electrical motor model was implemented in software. The new on-line parameter adaptation algorithm has been tested experimentally on three phase induction machine for a proof-of-concept demonstration. The developed algorithm for the three phase induction motor couple to dc motor provides fast convergence of parameters, rapid response characteristics of the drive, and accurate tracking of the control command for the three phase induction motor drive.These performance features are highly desirable for the propulsion motor in HEVs and EVs.